2021
DOI: 10.1021/acsanm.1c02002
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Plasmonic Response of AuGe Nanoparticles on GaAs Substrates: Implications for Photodetectors

Abstract: We present an integral study on the photonic response of AuGe nanoparticles (NPs) to establish a correlation between different parameters such as NP size, volume, and distribution over different substrates (n + GaAs, semiconducting GaAs) having different film thicknesses (∼5, ∼10 nm) at different annealing temperatures (573 and 673 K) subjected to repeated and stepped annealing cycles. The structural characterization of overlayer growth and formation of AuGe nanoclusters/ NPs is correlated with unusual plasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…[5][6][7][8][9][10][11] These studies have revealed unique photoresponse characteristics, including high photoresponsivity and ultrafast relaxation times, and it is also found that the occupied surface states often occur in the midgap of Bi 2 Se 3 , while unoccupied surface states emerge at higher energy levels, making Bi 2 Se 3 a promising candidate for optoelectronic applications. [12][13][14][15][16][17][18] Expanding on the potential of Bi 2 Se 3 and its surface states, the incorporation of a gold interlayer amidst topological layers may introduce an array of compelling functionalities. This interface not only influences and affects the surface charge density of the topological material but also modulates charge transfer dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] These studies have revealed unique photoresponse characteristics, including high photoresponsivity and ultrafast relaxation times, and it is also found that the occupied surface states often occur in the midgap of Bi 2 Se 3 , while unoccupied surface states emerge at higher energy levels, making Bi 2 Se 3 a promising candidate for optoelectronic applications. [12][13][14][15][16][17][18] Expanding on the potential of Bi 2 Se 3 and its surface states, the incorporation of a gold interlayer amidst topological layers may introduce an array of compelling functionalities. This interface not only influences and affects the surface charge density of the topological material but also modulates charge transfer dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast transient spectroscopy is the key tool that makes it simple to comprehend and visualize all of the aforementioned factors. Carrier dynamics and recombination behavior of Sb 2 Se 3 in a single crystal and deposited thin films were examined in a series of studies undertaken by various researchers. Grad et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] To determine the various type of EPI, different experimental and theoretical approaches are used to extract information about both the strength of the EPI and the energy of the involved phonons, such as angle‐resolved photoemission spectroscopy (ARPES), helium‐atom scattering, and Raman spectroscopy and ultrafast transient absorption spectroscopy (UFTS). [ 4,11 ] The ARPES is a fundamental technique that directly probes quasiparticle properties, while the time‐resolved ARPES or pump‐probe experiments access ultrafast carrier dynamics. [ 12–14 ] Richter et al.…”
Section: Introductionmentioning
confidence: 99%
“…[10] To determine the various type of EPI, different experimental and theoretical approaches are used to extract information about both the strength of the EPI and the energy of the involved phonons, such as angle-resolved photoemission spectroscopy (ARPES), helium-atom scattering, and Raman spectroscopy and ultrafast transient absorption spectroscopy (UFTS). [4,11] The ARPES is a fundamental technique that directly probes quasiparticle properties, while the time-resolved ARPES or pump-probe experiments access ultrafast carrier dynamics. [12][13][14] Richter et al investigated phonons of Bi 2 Se 3 , including phonon modes, for the first time using Raman spectroscopy while Irfan et al and Kim et al investigated the temperature-dependent frequency shift and linewidth of the A 2 1g and E 1g modes using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%